Die prediking oor die eindoordeel - Wyk, I. W. C. van (Hervormde teologiese studies, 1996)
Preaching on the last judgement.This article deplores the fact that the theologumenon 'last judgement' has become a museum piece. It seeks to stimulate a new debate on this topic. The author is convinced that this theologumenon is a central topic of the Jewish-Christian" religion and should therefore be actualised in such a way that it again can become part of the living faith of the church. The author enters into discussion with Moltmann about God's actions in this world, with Pannenberg about the criterion of the judgement and with Kung about eternal punishment.